Recuerdos de un viaje por España - Lafuente, Modesto
Contiene: 1T. Castilla, León Oviedo, Provincias Vascongadas, Asturias 2 T. Galicia, navarra, La Rioja, Aragon, Cataluña y Valencia 3 T. Andalucía, estremadura, Castilla la nueva y Madrid